Business Model in Plasma Nano Bubble Technology For Palm Oil Waste Processing - Arif Imam Suroso; Anto Tri Sugiarto; Yohanes Aris Purwanto; Popong Nurhayati; Nur Hasanah; Anita Primaswari Widhiani; Khairiyah Kamilah; Muchamad Bachtiar; Raden Isma Anggraini; Fithriyyah Shalihati; Hansen Tandra (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: The palm oil industry strives to implement sustainable development, maintaining the environmental quality. However, the palm oil industry has problems processing liquid waste, often known as palm oil mill effluent (POME), since it could pollute the environment. This waste also requires a large costs to be processed. On the other hand, there is potential economic value from liquid waste to be processed into several products, namely biogas, organic fertilizer, and refining value-added compounds. Currently, POME waste processing innovation could be conducted by applying plasma nanobubble (PNB) technology. This creates opportunities for a business that is engaged in developing this technology.Purpose: The aim of this research is to analyse the business model of the Plasma Nano Bubble (PNB) technology development business for the palm oil industry. Design/methodology/approach: This research uses the Business Model Canvas (BMC) to map the business processes of the Plasma Nano Bubble (PNB) technology development.Findings/Result: This study indicate that the most prominent attribute exhibited by PNB technological enterprises is their value offer, which is demonstrated by their ability to deliver efficient processing time and cost effectiveness, resource efficiency, adherence to government regulations, and the establishment of strategic collaborations with external entities. Meanwhile, the weakest element is customer relations, as only long-term relationships, and the provision of intensive training for PNB technology resellers were found in this aspect. Several indicators were proposed to improve the business model of PNB's technology, namely key partnership, the key activity, value proposition, and customer relationship.Conclusion: This research gives an important contribution related to the environmental benefits of implementing this business. The continuous development for this technology needs to be implemented to process POME waste effectively and efficiently.Originality/value (State of the art): The state of the art of this research is the development of business models for environmentally friendly products in the palm oil sector, which is currently rarely conducted, in this case the study of PNB technology products. Keywords: business model canvas, palm oil, plasma-nano bubble (pnb) technology, sustainable development, palm oil waste